Urban party zones and their changes in former communist countries on the example of Polish cities - Iwanicki, Grzegorz; Dłużewska, Anna (Bulletin of Geography. Socio-economic Series, 2020)
Former communist countries which in 2004 joined the European Union have recently become popular party tourism destinations. In connection with social and economic transformations following the fall of communism, a public space with the densest concentration of clubs was formed in the centres of big cities. Such a space can be called a party zone. This paper presents such zones delimited in Polish cities and attempts to investigate changes in those zones in 2004-2017, so after the accession to the EU. An additional objective was identifying the most popular clubs based on information from social media and deriving from interviews with DJs. The results lead to two main conclusions: (a) three main types of party zones can be identified in the analyzed cities taking into account their form and relationship to urban space; (b) in 2004-2017 the preferences of clubbing users changed for the benefit of open air clubs.